Respuesta :
Answer:
(a) [tex]8 x(5 x-6)=40 x^{2}-48 x[/tex]
(c) [tex]\begin{aligned}(x-3)(5 x-6) &=5 x^{2}-21 x+18\end{aligned}[/tex]
Step-by-step explanation:
(a) To find verify the answer we need to multiplying the equation [tex]8 x(5 x-6)[/tex]
[tex]8 x(5 x-6)=40 x^{2}-48 x[/tex]
Thus, this statement is true.
(b) To find verify the answer we need to multiplying the equation [tex]-4 x\left(2 x^{2}+1\right)[/tex]
[tex]-4 x\left(2 x^{2}+1\right)=-8 x^{3}-4 x[/tex]
Hence, the given statement is false.
(c) To find verify the answer we need to multiplying the equation [tex](x-3)(5 x-6)[/tex]
[tex]\begin{aligned}(x-3)(5 x-6) &=5 x^{2}-6 x-15 x+18 \\&=5 x^{2}-21 x+18\end{aligned}[/tex]
Hence, the given statement is true.
(d) To find verify the answer we need to multiplying the equation[tex](2 x+3)\left(x^{2}+3 x-5\right)[/tex]
[tex]\begin{aligned}=(2 x+3)\left(x^{2}+3 x-5\right) &=2 x^{3}+6 x^{2}-10 x+3 x^{2}+9 x-15 \\&=2 x^{3}+9 x^{2}-x-15\end{aligned}[/tex]
Hence, the given statement is false.